The Influence of Auguste Comte’s Philosophy in the Pedagogy of Ákos Pauler (Training and Practice : Journal of Educational Sciences, 2009)
The philosophy of Auguste Comte was involved and became well known in East Europe particularly in Hungary.There were a lot offollowers of his philosophy still the World War I. One of his followers was Akos Pauler (1876-1933) in the field of pedagogy although he criticised his philosophy. His grandfather, Tivadar Pauler (1816-1886) was minister of education after baron József Eötvös and could realise his education’s law, which begun in 1868. Akos Pauler’s father, Gyula Pauler (1841-1903) was the famous historian positiviste as a follower of Comte, who became the founder of National Archives of Hungary and he was academic. Akos Pauler could read Comte’s ideas not only at home, because his teachers of the University of Budapest Frigyes Medveczky (1855-1914), Alexander Berndt (1850-1927) were followers of Auguste Comte too.